Craniomaxillofacial trauma in immature dogs–etiology, treatments, and outcomes - Wolfs, Elias; Arzi, Boaz; Guerrero Cota, Jose; Kass, Philip H.; Verstraete, Frank J. M. (Frontiers in Veterinary Science, 2022)
Treatment of craniomaxillofacial (CMF) trauma in dogs often requires a multidisciplinary approach and a thorough understanding of the CMF anatomical structures involved. This retrospective study aimed to utilize computed tomography (CT) studies of immature dogs evaluated for CMF trauma and to describe common fracture locations, treatment modalities, and complications, as well as the fracture healing outcomes. The medical records and CT studies of 94 dogs under 1 year of age over a 13-year period were evaluated. The skeletal location of CMF fractures, as well as the severity of displacement and fragmentation of each fracture, was recorded. Case demographic data and trauma etiology were also recorded. Animal bites accounted for the majority of trauma (71.0%). The most likely bone or region to be fractured was the maxillary bones, followed by the molar region of the mandibles. Up to 37 bones or specific regions were fractured in any given patient, with an average of 8.8 ± 3.1 fractured bones or regions per dog. Rostral mandibular trauma was associated with intra-articular fractures of the temporomandibular joint (p = 0.016). Patients sustained concomitant injuries in 32% of the cases. Muzzle therapy was the main treatment performed for most dogs (53.2%), followed by soft tissue closure (47.9%) and selective dental extractions (27.6%). Healing complications were recorded in 71.6% of the dogs, with malocclusion being the most reported complication (55.2%), and associated with dentate mandibular jaw fractures (p = 0.05). The average number of complications per dog was 2.4. No statistically significant association was found between treatment modality and healing outcome. There was a positive correlation between the severity of fracture fragmentation and displacement and a negative healing outcome (all rho >0.7). Further treatment was required in 55.6% of the dogs. Additional dental extractions were performed in 77.7% of patients. Healing complications were common in the immature CMF trauma case. Thus, the need for a comprehensive assessment of the entire CMF region during the initial visit, as well as follow-up, preferably using CT or cone beam CT, is underscored.